Diversifying agrifood systems to ensure global food security following the Russia–Ukraine crisis - Neik, T. X.; Siddique, K. H. M.; Mayes, S.; Edwards, D.; Batley, J.; Mabhaudhi, Tafadzwanashe; Song, B. K.; Massawe, F. (Frontiers Media, 2023)
The recent Russia–Ukraine conflict has raised significant concerns about global food security, leaving many countries with restricted access to imported staple food crops, particularly wheat and sunflower oil, sending food prices soaring with other adverse consequences in the food supply chain. This detrimental effect is particularly prominent for low-income countries relying on grain imports, with record-high food prices and inflation affecting their livelihoods. This review discusses the role of Russia and Ukraine in the global food system and the impact of the Russia–Ukraine conflict on food security. It also highlights how diversifying four areas of agrifood systems—markets, production, crops, and technology can contribute to achieving food supply chain resilience for future food security and sustainability.